PRODUKSI TRIACETIN DENGAN PROSES ESTERIFIKASI GLISEROL DAN ASAM ASETAT MENGGUNAKAN KATALIS ASAM SULFAT - Ika Windrianto K. H; Hantoro Satriadi (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Biodiesel is one alternative energy that is expected to replace diesel fuel. Glycerol is a by product of biodiesel production from transesterification reaction. Glycerol when esterified with acetic acid to form triacetin. Triacetin usability very much both for food and non food. For groceries, triacetin can be used as a fragrance ingredient in candy, beverages from milk, soft drinks and chewing gum. As for the non-food materials can be used for solvent triacetin on perfumes, printing ink, solvent in flavor, plasticizer for cellulose resin, polymer and co-polymers, it can even be used as fuel additives to reduce knocking in car engines. In this study will be obtained under optimum conditions of manufacture of triacetin. Glycerol and total volume of 600 ml acetic acid, stirring speed of 100 rpm and the catalyst was 5 wt% glycerol. In this study the process of qualitative analysis using FTIR instrument has detected the existence of triacetin product. Besides the quantitative analysis obtained under optimum conditions resulted in mole ratio of reagents 1:7 glycerol and acetic acid to a temperature of 1200C at 5 minutes with the conversion rate of 67.6323 %.